Dark-Bright Soliton Bound States in a Microresonator - Zhang, Shuangyou; Bi, Toby; Ghalanos, George N.; Moroney, Niall P.; Del Bino, Leonardo; Del'Haye, Pascal (Physical Review Letters, 2022)
Dissipative Kerr solitons in microresonators have facilitated the development of fully coherent, chipscale frequency combs. In addition, dark soliton pulses have been observed in microresonators in the normal dispersion regime. Here, we report bound states of mutually trapped dark-bright soliton pairs in a microresonator. The soliton pairs are generated seeding two modes with opposite dispersion but with similar group velocities. One laser operating in the anomalous dispersion regime generates a bright soliton microcomb, while the other laser in the normal dispersion regime creates a dark soliton via Kerr-induced cross-phase modulation with the bright soliton. Numerical simulations agree well with experimental results and reveal a novel mechanism to generate dark soliton pulses. The trapping of dark and bright solitons can lead to light states with the intriguing property of constant output power while spectrally resembling a frequency comb. These results can be of interest for telecommunication systems, frequency comb applications, and ultrafast optics.
CRIS-Team WoS Importer:2022-02-11